Complex myomectomy: A case report and literature review (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: Myomectomy is the surgical removal of fibroids with the preservation of the uterus for future childbirth. It may be complex when adhesions, multiple myomas of different sizes are present in various sites, and a repeat myomectomy.Case presentation: A 40-year-old nulliparous presented with primary infertility. She reported having heavy and prolonged menstrual bleeding that led to multiple blood transfusions due to symptomatic anemia. Physical examination revealed a palpable mass that was irregular, mobile, non-tender. Her fundal height was 16 weeks. Pelvic ultrasound demonstrated multiple uterine fibroids of varying sizes and locations. The patient desired fertility and was therefore scheduled for myomectomy. A total of 80 fibroids were excised. Tourniquet and vasopressin were used to reduce hemorrhage. Bilateral uterine artery ligation was done to achieve hemostasis.Conclusion: Myomectomy complicated by multiple myomas up to 80 in number is possible. However, a meticulous surgical technique of myomectomy by an experienced surgeon is required. The use of tourniquet and vasopressin is vital to reduce hemorrhage during the operation.